Addressing Disparities in Transplant Medicine: Proposing a Strategic Framework for Japan - 田邊, 一成; 日高, 寿美; 大久保, 恵太; 小林, 修三 (移植, 2024)
**Purpose:**This discourse examines the disparity in transplant medicine between the U.S. and Japan. While the U.S. has abundant access to treatments, Japan lacks this, leading to avoidable deaths. The aim is to propose a framework inspired by U.S. practices to enhance transplant medicine in Japan.**Method:**A quantitative comparison reveals a stark difference in organ donation rates: the U.S. has 12,000 donors annually, whereas Japan has only around 100. This highlights differences in donation willingness and the lack of a robust transplantation infrastructure in Japan. Further analysis of economic incentives in American transplantation medicine provides valuable insights.**Results:**Japan has approximately 850 organ donation facilities, but stringent requirements limit accessibility, especially for brain death determination. In contrast, the U.S. has streamlined the process with dedicated donor centers in each state.**Conclusion:**Japan's transplant medicine lacks active promotion and incentivization. Establishing a comprehensive system and considering donor centers for brain death determination could improve accessibility and advance transplantation medicine in Japan